Eksplorasi Perintang Warna Alami pada Kualitas Batik - Sulistyorini, Urip Wahyuningsih, Rani (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2021)
Exploration is important because it has the potential to increase creativity in the use of natural materials that are able to maintain the existence of written batik without reducing the essence of written batik itself. The method used is a literature study. This study aims to describe natural materials that can be used as color barriers, determine the results and quality of batik motifs produced from natural color barriers, and determine the process and results of batik coloring on natural color barriers. The natural ingredients explored are cassava peel and canna starch. The batik motifs produced by the two barriers depend on the drying time, the thickness of the paste application and the applicator used. In the use of natural cassava peel ingredients, the color barrier can block the color well when using a triangular plastic applicator because the quality obtained is good, namely the lines are firm and clear. Meanwhile, when using natural canna starch, the color barrier can block the color well when using the vinegar bottle applicator because the results of the imitation batik motifs produced are neat, even, and firm. The natural ingredients for cassava peel are dylon and wantex dyes, while the canna starch is used for napthol dyes.